Ferns and lycophytes from municipality of Caxias, state of Maranhão, Brazil - Fernandes, Rozijane Santos; Conceição, Gonçalo Mendes da; Costa, Jeferson Miranda; Paula-Zárate, Eliete Lima de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
This study presents an inventory of the ferns and lycophytes from the Caxias municipality (Maranhão State, Brazil), which is the second work with these plant groups in the state. Whereas plants are very poorly sampled in Maranhão, we understand to be important to study the floristic composition of these groups for the knowledge of plant diversity as a whole. The municipality has 531,350 ha of area and is located in the eastern side of the state, where the vegetation cover is characterized by the contact between cerrado and forest. The material was collected between November 2005 and August 2007. The 21 registered species belong to 14 genera and 11 families, among which the richest was Pteridaceae (five species), followed by Thelypteridaceae (four species). Six species were cited as new registers to Maranhão [Selaginella erythropus (Mart.) Spring, S. flagellata Spring, Acrostichum danaeifolium Langsd. & Fisch., Adiantum serratodentatum Humb. & Bonpl. ex Willd., Lindsaea divaricata Klotzsch and Salvinia auriculata Aubl.]. The majority of the species was terrestrial, occurred inside the forests and presented American distribution.
Keywords: Floristic; Ferns; Northeastern Brazil